2012
DOI: 10.1538/expanim.61.555
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Levels on Sex Hormones in Growing Male Rats Kept under Constant Darkness

Abstract: Abstract:The purpose of this experiment was to clarify the effects of dietary protein levels on the gonadal development and sex hormones in male rats kept under constant darkness as a model of disturbed daily rhythm. Four-week-old male rats (Fischer 344 strain) were kept under constant darkness or normal lighting (12-h light/dark cycle). Two kinds of experimental diet were prepared, one with low dietary protein levels (9% casein) and one with normal levels (18% casein). Harper mineral mixture and Panvitan were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…We have been investigating the effects of various nutrients on sexual organ development in rats kept under constant darkness (5)(6)(7)(8)(9)(10)(11)(12). The present study used a model in which the daily rhythm was free-running rather than a 24-h rhythm.…”
mentioning
confidence: 99%
“…We have been investigating the effects of various nutrients on sexual organ development in rats kept under constant darkness (5)(6)(7)(8)(9)(10)(11)(12). The present study used a model in which the daily rhythm was free-running rather than a 24-h rhythm.…”
mentioning
confidence: 99%
“…Yet, the direction of this influence remains unclear due to contradicting results found in the literature. A few experimental studies have reported that a low-protein diet can lead to low levels of T in male rat models [39,40], but an inverse association was found between protein and T levels in a number of population-based studies [25,41]. Interestingly, more recent literature has focused mainly trying to compare and assess the effects on T levels by different types of proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example several studies show that prolonged darkness phase in photoperiodic cycle causes decreased serum level of T3 [16], [17], whereas there is a study indicating that prolonged darkness phase has no effect on secretion of T3 hormone [18]. The probable mechanism of action could be referred to the effect of prolonged darkness phase on systems such as immunity and gonadal system [19]- [21], which in turn, may result in increased serum level of creatine kinase and alkaline phosphatase. On the other hand experiences show that prolonged darkness phase causes increased melatonin secretion and pineal activity [16] and this may also lead to increased serum level of creatine kinase and alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%